1. simple keep change change, changing it from -2--3 to -2+3=1 or to switch that order to make it even easier on yourself you can make it 3-2=1 but be careful with your signs when switching the order of numbers in the equation. the answer is 1.
-3 1/3 minus -5 2/3 = 2 1/3
-3 and 2/3
2 - (-3) = 5 (The minus a negative becomes a positive, thus 2 + 3 = 5).
negative 1/3
-3 minus -28 is 25
-3 minus -2 is -1.
negative 3
3. positive 3
-3 1/3 minus -5 2/3 = 2 1/3
-3 and 2/3
2 - (-3) = 5 (The minus a negative becomes a positive, thus 2 + 3 = 5).
negative 1/3
-3 minus -28 is 25
Two (2) minus negative three (-3) is five (5). When you subtract a negative number it is the same as adding a positive number of the same absolute value.
-2 - +3 = -5
One minus one third is two thirds. 1=3/3 3/3-1/3=2/3
negative 9 divided by negative 3 is 3 andnegative 3 minus 1 is negative 2